Comparative Study on Stomach Content Analysis of Caged and Free Living Puntius schwanefeldii in the Koto Panjang Dam, Kampar Regency Riau - Anggi Erywiyani Hasibuan; Deni Efizon; Efawani Efawani (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Puntius schawanefeldii is one of common fish in the Koto Panjang Dam. This fish commonly present around the floating cage culture area. Small P. schawanefeldii sometimes enter the culture cages and become trapped in the cages as they grew up. Farmers used to remove the trapped fish and put them in the cage around the cage culture area. The net caged P. schawanefeldii were not given any food, but they were able to grow. To understand the feed consumed by the caged fish and compare it with the free living fish, a study on the stomach content analysis of the caged and free living fish has been conducted on September 2022. Samplings were conducted 2 times, once/2 weeks and the stomach contents was analyzed using a volumetric method. There were 139 fishes captured. The stomach 104 fishes were full or partly full, while the stomach content of other 35 fishes were less than 25% and could not be analyzed. Results shown the stomach content of the caged and free living fish were similar, there were algae and pellets (they could not be separated), fish feed pellet remains and fish tissue remains. The Preponderance Index of each food type present in the caged fish are pellets 71.24%, mixed algae and pellets 26.76% and fish tissue remains 2.00%, while those of the free living fish are pellets 16.28%, mixed algae and pellets 70.63%, and fish tissue remains 11.44%. Data obtained in this research indicate that the caged fish receive fish feed pellets that spilled out from the culture floating nets in the surrounding area.